Robust Utkin’s Observer Based Controller for Deregulated Hydro-Thermal LFC Problem (International Journal of Engineering and Computer Science, 2015)
This paper presents a new nonlinear observer based control strategy popularly known as Utkins observer based controller has been proposed to solve load frequency control of a multi area Hydro-Thermal deregulated system. The proposed control strategy has inherent capabilities to tackle certain nonlinearities and uncertainties of the highly non linear power system. The performance of Utkins observer based controller is tested on two area Hydro-Thermal deregulated power system including bilateral contacts when system is subjected to sudden disturbance. The dynamic response of the system with proposed Utkins observer based controller is compared with dynamic response of the system with Conventional PI controller.